The transnationalization of corruption and the use of the penal procedure as a political tool - Ricardo Jacobsen Gloeckner; Felipe Lazzari da Silveira (Revista Brasileira de Direito Processual Penal)
This article questions the involvement of the fight against corruption and the neoliberal rationality, as well as the consequences brought by this interaction to the criminal procedure, mainly its use as a political tool. This theoretical endeavor is due to the discoveries of Operação Lava Jato, in good part to the use of old and new punitive ideologies that tend to aggravate the criminal justice system and its influence in the political-governmental scenario. Concerning the facts previously mentioned, and considering that corruption cannot be reduced under the suppression of procedural rights and guarantees, this paper aims at showing that the anti-corruption campaigns have been of great relevance to stimulate the neoliberal project. Regarding Brazil, these campaigns have helped prevent the democratization of the penal procedure field.  For this purpose, this paper is going to present the origin of transnationalization of corruption through a bibliographic and documental analysis. In four topics, the present paper is going to demonstrate the connection of anticorruption campaigns to the neoliberals’ intentions, and establish the determinant role played by the fight against corruption, which started in Brazil in 2014, to the strengthen of authoritarian characteristics of the criminal procedure, as well as to its political use.